2022
DOI: 10.1002/1873-3468.14312
|View full text |Cite
|
Sign up to set email alerts
|

The key role of ergothioneine in label‐free surface‐enhanced Raman scattering spectra of biofluids: a retrospective re‐assessment of the literature

Abstract: Label-free surface-enhanced Raman scattering (SERS) has recently gained attention in the field of liquid biopsy as a rapid and relatively inexpensive technique that could significantly ease clinical diagnosis and prognosis by investigating a biofluid sample with a laser. Indeed, SERS spectra provide information about a set of metabolites present in the analysed biofluid, thereby offering biochemical insight into specific health conditions. Ergothioneine plays a key role since it is one of the few metabolites i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Research has shown that when employing these substrates with a near-infrared excitation wavelength of 785 nm, the most prominent bands observed in SERS mainly correspond to molecules associated with purine metabolism (such as uric acid, hypoxanthine, and xanthine), glutathione, and proteins (in the case of unfiltered, whole biofluids) [ 20 , 22 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. More recently, the presence of ergothioneine (ET), a dietary amino acid with a speculated vitamin-like role, has also been detected using SERS in biofluids [ 39 , 42 ]. Furthermore, it is worth noting that the use of lower wavelength laser excitations (532 nm and/or 633 nm) primarily leads to the occurrence of vibrational bands specific to carotenoids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that when employing these substrates with a near-infrared excitation wavelength of 785 nm, the most prominent bands observed in SERS mainly correspond to molecules associated with purine metabolism (such as uric acid, hypoxanthine, and xanthine), glutathione, and proteins (in the case of unfiltered, whole biofluids) [ 20 , 22 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. More recently, the presence of ergothioneine (ET), a dietary amino acid with a speculated vitamin-like role, has also been detected using SERS in biofluids [ 39 , 42 ]. Furthermore, it is worth noting that the use of lower wavelength laser excitations (532 nm and/or 633 nm) primarily leads to the occurrence of vibrational bands specific to carotenoids.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few papers compare the SERS signals of blood serum or plasma with those of relevant molecules obtained under the same experimental conditions. These conditions include the use of the same substrate, excitation wavelength, and ionic composition of the medium, among others [ 20 , 22 , 39 , 42 ], and our tentative assignments are based on these references together with combined experimental and theoretical papers related to SERS of uric acid [ 43 ] and hypoxanthine [ 44 ], as will be detailed further.…”
Section: Resultsmentioning
confidence: 99%
“…The affinity of the molecules toward the plasmonic substrate plays a crucial role in the recording process of SERS spectra. Very recently, it has been shown that there is a strong possibility that much of the SERS spectra collected on blood samples reported so far in the literature are dominated by a dietary amino acid (ergothioneine) that has a great affinity for the plasmonic substrates used in SERS experiments [22]. In order to reduce the possibility of the occurrence of such experimental artifacts, all the spectra included in this study have been recorded on solid plasmonic substrates prepared using a procedure developed in our laboratory that proved their capacity to generate specific and reproducible SERS spectra of blood plasma and serum based on their ability to act as a "spectroscopic filter" [18].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Fornasaro et al, 2021, have shown that ergothioneine, which is a dietary amino acid present in different biological samples, has a great impact on the SERS spectra collected on various biofluids (e.g., erythrocytes lysates, serum, gingival crevicular fluid, seminal plasma, cerebrospinal fluid). This phenomenon may occur due to its high affinity for the plasmonic substrates, highlighting once more the major role played by the nanoscale interactions of the biomolecules with the plasmonic nanostructure in SERS analysis [22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are many facets of ET biology yet to be explained, such as its presence at exceptionally high levels in the seminal fluid of stallions and boars, much less in this fluid from other species [45], and its possible involvement in human development, as seen from the ability of mothers to pass ET to the baby (discussed in [46]). Indeed, these are exciting times for the ET field, including new methods to identify [49] and produce [50] it. We hope that this special issue of FEBS Letters will raise awareness of this unique compound.…”
Section: Figmentioning
confidence: 99%